Glucagon-like peptide-1 receptor agonist attenuates diabetic neuropathic pain via inhibition of NOD-like receptor protein 3 inflammasome in brain microglia. (April 2022) - Zhang, Qi; Li, Qingchun; Liu, Siying; Zheng, Hangping; Ji, Lijin; Yi, Na; Bao, Weiqi; Zhu, Xiaoming; Sun, Wanwan; Liu, Xiaoxia; Zhang, Shuo; Zuo, Chuantao; et al.
Highlights: Brain microglial activation in DNP rats was observed by PET/CT with [18F]-DPA-714 as a dedicated radiotracer. GLP-1RA significantly alleviated mechanical and thermal pain in rats with DNP via intracerebroventricular injection. GLP-1RA suppressed the activation of NLRP3 inflammasome in microglia. Abstract: Aims: We aimed to explore the evidence of brain microglia activation in diabetic neuropathic pain (DNP) and the effect and mechanism of glucagon-like peptide-1 receptor agonist (GLP-RA) on DNP via brain microglia. Methods: Brain microglia activation was observed in DNP rats by positron emission tomography/computed tomography. The behavior of neuropathic pain was assessed in DNP rats after intracerebroventricular administration of GLP-1RA or microglial inhibitor minocycline. RNA sequencing was performed to explore the target of GLP-1RA on brain microglia. NOD-like receptor protein 3 (NLRP3) expression in brain microglia was evaluated in mentioned-above DNP rats, and the activation of NLRP3 inflammasome was analyzed in microglia treated with GLP-1RA. Results: Microglia were activated in the cortex and thalamus of DNP rats. The thermal and mechanical allodynia were alleviated in DNP rats via intracerebroventricular administration of GLP-1RA or minocycline. And the activation of brain microglia was attenuated in DNP rats by intracerebroventricular administration of GLP-1RA. The expression of NLRP3 in brain microglia, which was found by RNA sequencing, was reduced in DNP rats by administration of GLP-1RA. Furthermore, GLP-1RA attenuated NLRP3 inflammasome activation in microglia triggered by LPS. Conclusion: GLP-1RA could alleviate DNP, possibly mediated by the suppression of brain microglia NLRP3 inflammasome activation.